2022
DOI: 10.1108/ijoem-04-2021-0639
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence of the relationship between terrorism and firm financial performance in Nigeria

Abstract: PurposeThis paper investigates the relationship between terrorism and firm financial performance in Nigeria. The country has become one of the riskiest countries in Sub-Saharan Africa due to the intensity of recent terror attacks. Also, there is a growing focus on the importance of firms, given firms' economic contribution towards growth, employment and economic and industrial transformation. However, no study has tried establishing a relationship between terrorism and firm financial performance. Therefore, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…The macrolevel data on terrorism was collected from the global terrorism database. To establish the discriminant and convergent validity of the measures (Henseler et al, 2015), a standardized survey instrument was employed with an identical sampling methodology to produce comparable data across firms and countries and minimize any potential error (Okafor & Calderon, 2022). Additionally, the global terrorism database reports the country-specific number of terror attacks and collects data daily.…”
Section: Tablementioning
confidence: 99%
See 4 more Smart Citations
“…The macrolevel data on terrorism was collected from the global terrorism database. To establish the discriminant and convergent validity of the measures (Henseler et al, 2015), a standardized survey instrument was employed with an identical sampling methodology to produce comparable data across firms and countries and minimize any potential error (Okafor & Calderon, 2022). Additionally, the global terrorism database reports the country-specific number of terror attacks and collects data daily.…”
Section: Tablementioning
confidence: 99%
“…Likewise, Shahzad et al (2017) reported the negative association of terrorism with industry performance based on the research conducted among Pakistanis equity industries from 2000 to 2014. In addition, a recent study conducted among Nigerian manufacturing firms by Okafor and Calderon (2022) reported the significant influence of terrorism on a firm's financial performance. Likewise, Mazhar and Rehman (2021) analyzed the influence of terrorism on manufacturing firms in Pakistan.…”
Section: Financial Performance and Terrorismmentioning
confidence: 99%
See 3 more Smart Citations